Synthesis of novel families of conductive cationic poly(ionic liquid)s and their application in all-polymer flexible pseudo-supercapacitors. (10th August 2018) - Ponkratov, Denis O.; Lozinskaya, Elena I.; Vlasov, Petr S.; Aubert, Pierre-Henri; Plesse, Cédric; Vidal, Frederic; Vygodskii, Yakov S.; Shaplov, Alexander S.
Abstract: This paper deals with the synthesis of two new families of cationic poly(ionic liquid)s (PILs). The first one is obtained by free radical copolymerization of 1-[2-(2-(2-(methacryloyloxy)ethoxy)ethoxy)ethyl]-3-methylimidazolium bis(trifluoromethylsul-fonyl)imide with poly(ethylene glycol) methyl ether methacrylate, while the second one by chemical modification of poly(epichlorohydrin- co -ethylene oxide) via quaternization with N-methylimidazole and subsequent ion exchange with lithium bis(trifluoromethylsulfonyl)imide. Both PILs demonstrated Tg below 0 °C, bulk ionic conductivities in anhydrous state in the range of 8.4 × 10 −7 -1.5 × 10 −5  S/cm (25 °C) and electrochemical stability of 3.1–3.4 V (25 °C). These PILs were further applied in the construction of symmetric truly all-polymer pseudo-supercapacitors. The first PIL, possessing high ionic conductivity of 1.5 × 10 −5  S/cm at 25 °C, was chosen to play the role of separator, while the second one, demonstrating an ability to form good coatings, was used for the preparation of the thin electrode films via vapor phase polymerization of 3, 4-ethylenedioxythiophene (EDOT), pyrrole (Py) or 3-methylthiophene (3 MT) in its solution. The varying of the electroactive polymer's nature allowed for the optimization of the devices parameters resulting in the assembly of PPy+PIL2/PIL1/PPy+PIL2 pseudo-capacitor showing best characteristics in terms of specific capacitance (2.8 and 7.0 F/g at 30 mV/s scan rate and 25 and 70 °C, respectively), energy and power (Emax  = 1.39 Wh/kg and Pmax  = and 286 W/kg at 70 °C and 30 mV/s scan rate). Such flexible device was cycled for 1000 cycles with 96% of capacitance retention at a voltage up to 1.2 V at 25 °C. To be clear, this level of electrochemical performance is not as high as other systems that have been reported in the literature. However, we emphasize that the novelty of these proof-of-concept experiments is the fact that they demonstrate the possibility, for the first time and to the best of our knowledge, to create pseudo-supercapacitors based on polymeric materials alone, with no low molecular weight components. This is significant because it represents a path to highly efficient, lightweight and safe devices requiring no sealing and tolerant of a much broader range of application conditions (reduced pressures, high temperature, etc.).